Hardiness on burnout : the mediating role of work stress - Fitri Nevita; Mega Asri Zona (Human Resource Management Studies, 2022)
This study plans to break down the impact of hardiness on burnout at the Office of the Ministry of Religion in West Pasaman with work stress as an interceding variable. The sort of exploration utilized is quantitative examination. This exploration is a causal examination. The populace in this study were each of the 36 representatives of the Ministry of Religion of West Pasaman. The inspecting strategy utilizes soaked testing where all individuals from the populace are utilized as tests. Gathering information utilizing a poll with a Likert scale. The strategy for examination utilizing Partial Least Square utilizing the Smart PLS program. The after effects of information handling in this study demonstrate that: (1) hardiness has a negative and significant effect on burnout at the Ministry of Religion Office in West Pasaman (2) hardiness has a positive and significant effect on work stress at the Ministry of Religion Office in West Pasaman (3) work stress has an effect positive and significant effect on burnout at the Ministry of Religion Office in West Pasaman (4) hardiness has a positive and significant effect on burnout through work stress at the Ministry of Religion Office in West Pasaman